Refining stereotactic body radiation therapy as a bridge to transplantation for hepatocellular carcinoma: An institutional experience. Issue 3 (24th February 2023) - Chen, Beini; Butler, Nick; O'Rourke, Thomas; Hodgkinson, Peter; Stuart, Katherine; Shih, Edwin; Leggett, David; Pryor, David; Liu, Howard; Lee, Dominique
Abstract: Background: Stereotactic body radiotherapy (SBRT) has been established as a safe and effective treatment for hepatocellular carcinoma (HCC). Currently, there are no consensus guidelines to advise optimal patient selection and radiotherapy planning parameters to minimise the risk of surgical and medical complications after liver transplant (LT) in patients who have had prior SBRT for HCC, whilst optimising treatment benefit. Methods: We performed a retrospective analysis of all adult patients who received liver SBRT as a bridge to LT at a tertiary institution between 2017 and 2019. Results: Nine patients received SBRT as bridging therapy to LT. HCC location varied from peripheral to central/hilar regions and HCC diameter was 13–54 mm. Median time between SBRT and LT was 141 days (range 27–461 days). Median operating time was 360 min (range 270–480 min). Four patients (44%) had visible SBRT reaction or fibrosis at the time of LT. SBRT reaction resulted in clinical impact in one patient (11%) only, where vascular clamping of the IVC was required for 10 min. Conclusion: SBRT is a safe and effective treatment for HCC enabling patients to remain within LT criteria, even for lesions not amenable to other more conventional bridging therapies. We describe a preliminary decision pathway to guide the optimal use of SBRT as a bridge to LT developed in our institution.